Upaya Penurunan Kecemasan Pada Pasien Kanker Payudara yang Menjalani Kemoterapi di RSMH Palembang - Alvian Harisandy; Selamat Parmin (Yayasan Daarul Huda Kruengmane, 2026)
Cancer is a medical condition characterized by uncontrolled abnormal cell growth and the risk of spreading to other organs. One common treatment method is chemotherapy. However, this procedure often causes side effects such as nausea, insomnia, physical pain, and weight loss. If not managed properly, these side effects can trigger anxiety that risks hindering the effectiveness of the patient's recovery process. Providing education is one way to help raise public understanding regarding chemotherapy. This Community Service Program aims to reduce anxiety in breast cancer patients undergoing chemotherapy at RSMH Palembang. The methods used are lectures, discussions, and educational videos. Before and after the community service, questionnaires were administered to measure anxiety using the Hamilton Anxiety Rating Scale (HARS). Pre-test and post-test anxiety scores were analyzed using a Paired Samples T-Test to determine differences between before and after the intervention. The analysis results with a Paired Samples T-Test from 48 respondents obtained a P-value of 0.020, indicating a significant difference in the average anxiety scores of breast cancer patients undergoing chemotherapy before and after the intervention. Providing education can increase knowledge and reduce anxiety in breast cancer patients undergoing chemotherapy related to knowledge about chemotherapy starting from the definition, goals, and side effects, as well as handling the side effects of chemotherapy, as seen from the difference in anxiety scores that decreased before and after providing education.